Emergence of ciprofloxacin heteroresistance in foodborne Salmonella enterica serovar Agona. (3rd August 2020) - Zhang, Chuan-Zhen; Zhang, Yan; Ding, Xiao-Min; Lin, Xiao-Ling; Lian, Xin-Lei; Trampari, Eleftheria; Thomson, Nicholas M; Ding, Huan-Zhong; Webber, Mark A; Jiang, Hong-Xia
Abstract: Background: Bacterial heteroresistance has been increasingly identified as an important phenomenon for many antibiotic/bacterium combinations. Objectives: To investigate ciprofloxacin heteroresistance in Salmonella and characterize mechanisms contributing to ciprofloxacin heteroresistance. Methods: Ciprofloxacin-heteroresistant Salmonella were identified by population analysis profiling (PAP). Target mutations and the presence of PMQR genes were detected using PCR and sequencing. Expression of acrB, acrF and qnrS was conducted by quantitative RT–PCR. Competition ability and virulence were also compared using pyrosequencing, blue/white screening, adhesion and invasion assays and a Galleria model. Two subpopulations were whole-genome sequenced using Oxford Nanopore and Illumina platforms. Results: PAP identified one Salmonella from food that yielded a subpopulation demonstrating heteroresistance to ciprofloxacin at a low frequency (10 −9 to 10 −7 ). WGS and PFGE analyses confirmed that the two subpopulations were isogenic, with six SNPs and two small deletions distinguishing the resistant from the susceptible. Both subpopulations possessed a T57S substitution in ParC and carried qnrS . The resistant subpopulation was distinguished by overexpression of acrB and acrF, a deletion within rsxC and altered expression of soxS . The resistant population had a competitive advantage against the parental population when grown in the presence of bile salts but was attenuated in the adhesion and invasion of human intestinal cells. Conclusions: We determined that heteroresistance resulted from a combination of mutations in fluoroquinolone target genes and overexpression of efflux pumps associated with a deletion in rsxC . This study warns that ciprofloxacin heteroresistance exists in Salmonella in the food chain and highlights the necessity for careful interpretation of antibiotic susceptibility.